Rare case of circumaortic left renal vein with fenestration and nutcracker phenomenon - Jihaad, Fathmath Shajaa; Ali, Thalha; Maaha, Fathimath; Karpovich, Yulia; Bogdanovich, Vladimir (International Journal of Research in Medical Sciences, 2025)
Circumaortic left renal vein (CLRV) is a rare venous anomaly. It is usually clinically silent until discovered accidentally during an operation, imaging or an autopsy. Vascular fenestrations are most commonly seen in the arterial system or cerebral vessels and rarely in the venous system. Nutcracker phenomenon is usually associated with CLRV anomaly. We have described a case of a 31-year- old female who presented to the Department of Nephrology with CLRV, along with retro aortic renal vein fenestration and anterior nutcracker phenomenon. Since this variation is rarely diagnosed, it is important to have knowledge about such anomalies to rule it out as a differential diagnosis of haematuria. This information will also prevent iatrogenic injuries during surgical procedures.